Price relations between international rice markets - Adam John (Agricultural and Food Economics, 2014)
International rice markets are seen as volatile due to the thin nature of the market which is believed to be exacerbated by a low level of substitution between major rice export markets. In other words, this perceived lack of price transmission amongst international rice markets is believed to further thin out an already thin world rice market. The paper tests for price transmission between five major rice exporting markets representing Asia and the Americas over the past decade. It uses a vector autoregressive framework and performs Granger and Toda-Yamamoto causality tests and generalized impulse response functions to interpret the model's results. The findings suggest that price transmission exists across these major rice export markets with price relations being the most widespread between Asian markets. Furthermore, the direction of price transmission suggests that Asian prices act as price leaders for North and South American prices. While it is not clear whether there is a price leader amongst the Asian export markets, Vietnam has the most extensive price relations with other export markets which would suggest that the Vietnamese rice export price is a more suitable world reference price than the Thai export price. An implication of the presence of price relations between rice export markets is that the world rice market is not as fragmented as generally perceived in the literature. However, it can also explain why international rice prices are so sensitive to the volatile trading behavior of major markets.
Keywords: 330; Rice export markets; Price transmission; Causality tests; Impulse response functions; World reference price